2009
DOI: 10.1016/j.jacc.2008.08.070
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ventricular Assist Devices on Post-Transplant Mortality

Abstract: Extracorporeal VADs are associated with higher mortality within 6 months and again beyond 5 years after transplantation. Intracorporeal VADs are associated with a small increase in mortality in the first 6 months and a clinically significant increase in mortality beyond 5 years. These data do not provide evidence supporting VAD implantation in stable United Network for Organ Sharing status I patients awaiting heart transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(24 citation statements)
references
References 23 publications
0
22
2
Order By: Relevance
“…17 These findings contrast with those from a recent United Network for Organ Sharing Thoracic Registry analysis that reported higher mortality within 6 months and Ͼ5 years after transplantation in patients previously supported with extracorporeal and, although to a lesser extent, intracorporeal VADs. 18 Post-transplant survival in the present series was not influenced by the type of device used to provide biventricular support. However, there was a trend toward improved post-transplant survival in patients supported for 30 to 90 days compared with those undergoing short term (Ͻ30 days) or long term (Ͼ90 days) support (p ϭ 0.07).…”
Section: Discussionmentioning
confidence: 46%
“…17 These findings contrast with those from a recent United Network for Organ Sharing Thoracic Registry analysis that reported higher mortality within 6 months and Ͼ5 years after transplantation in patients previously supported with extracorporeal and, although to a lesser extent, intracorporeal VADs. 18 Post-transplant survival in the present series was not influenced by the type of device used to provide biventricular support. However, there was a trend toward improved post-transplant survival in patients supported for 30 to 90 days compared with those undergoing short term (Ͻ30 days) or long term (Ͼ90 days) support (p ϭ 0.07).…”
Section: Discussionmentioning
confidence: 46%
“…2 Their study may have been limited by incomplete LVAD data, however. In contrast, Russo and colleagues examined the UNOS database from 2001–2006 to determine if patients bridged to OHT had worse outcomes than patients undergoing conventional OHT.…”
Section: Resultsmentioning
confidence: 99%
“…There were early concerns that BTT patients would have inferior posttransplant survival compared with conventional OHT. 1, 2 However, contemporary devices have smaller profiles and improved reliability. 3 In the modern era of continuous flow (CF) devices, several reports suggest that patients bridged to transplant with CF LVADs appear to have equivalent or modestly inferior post-transplant survival compared to conventional OHT.…”
Section: Introductionmentioning
confidence: 99%
“…Survival post transplant in device patients has been the subject of several reports as multivariate analysis of large registry data has suggested that mechanical support is a predictive factor for poor transplant survival (12). More recent reports, which focused exclusively on long-term left ventricular assist device use as a bridge to transplant has refuted these observations (13,14).…”
Section: Discussionmentioning
confidence: 99%